The Effects of Topical Adenosine Agonists (Limonene) on Induced Ocular Hypertension in Rabbits - Amal Haitham Hameed (Journal of Global Pharma Technology, 2016)
Glaucoma is a multi factorial disease characterized by progressive loss of retinal ganglionic neurons, if glaucoma is not treated can progress to blindness. Controlling of intraocular pressure is the only approved medical therapy to decrease glaucoma progression. Limonene is a selective adenosine A2A receptors agonist, activation of this receptor can alter outflow resistance at the Schlemm’s canal cell level, and there by decrease IOP. Because vasodilatory effects of adenosine are primarily mediated by adenosine A1& A2A receptors. A fourth (40) rabbits (albino) included in this study &divided into 8 groups, travaprost 0.004% group A (n=8) used as positive control, isotonic buffer group B (n=8), limonene group C, D&E (1%, 2% and 4%) respectively (8) rabbits in each group. The present study was conducted to evaluate the intraocular pressures lowering effect of adenosine agonist (Limonene) and to explore their effect on adenylyl cyclase activity by measuring the level of cAMP changes in the aqueous humor in rabbits with induced ocular hypertension, and to explore the possible side effects of the tested agent on the eyes after instillation. The adenosine system is one of the potential target systems as new therapeutic approaches in glaucoma as concluded by the lowering IOP effect of limonene.Keywords: Intraocular pressure, Adenosine agonists, Limonene and travaprost.